2022
DOI: 10.3390/md20020104
|View full text |Cite
|
Sign up to set email alerts
|

A Dunaliella salina Extract Counteracts Skin Aging under Intense Solar Irradiation Thanks to Its Antiglycation and Anti-Inflammatory Properties

Abstract: Glycation, and the resulting buildup of advanced glycation end products (AGEs), is recognized as a key driver of cumulative skin damage and skin aging. Dunaliella salina is a halophile microalga adapted to intense solar radiation through the production of carotenoids. We present a natural supercritical CO2 extract of Dunaliella salina rich in the colorless carotenoids phytoene and phytofluene. The extract exhibited antiglycation and anti-inflammatory activities in ex vivo testing, showing strongly reduced form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A placebo-controlled study under extensive sun exposure, demonstrated a notable decrease in skin glycation scores and histamine sensitivity due to the application of, a halophile microalga [33]. Important indicators of skin aging, such as the number of wrinkles and spots, also demonstrated considerable improvement compared to the placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…A placebo-controlled study under extensive sun exposure, demonstrated a notable decrease in skin glycation scores and histamine sensitivity due to the application of, a halophile microalga [33]. Important indicators of skin aging, such as the number of wrinkles and spots, also demonstrated considerable improvement compared to the placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory effects were attributed to the decrease in NO, ROS, and IL-1β, thus decreasing LPS-induced cell death. Interestingly, the two studies with human subjects were performed with microalgae, where Phaeodactylum tricornutum supplements [106] showed good tolerance and improved inflammatory status and the modulation of intestinal permeability, and the skin application of Dunaliella salina demonstrated anti-inflammatory and anti-aging effects [107]. Polysaccharides were the only class of isolated compounds that exhibited anti-inflammatory action [108][109][110][111][112].…”
Section: Algal Applications In Managing Inflammatory Conditionsmentioning
confidence: 99%
“…Moreover, marine microorganisms such as microalgae, bacteria, and myxomycetes can be sources of antibacterial, antiviral, antitumoral, and antioxidant chemicals [ 180 , 186 ]. Thus, the extract from the green microalgae Dunaliella salina can prevent skin aging due to its anti-inflammatory and antiglycation properties [ 187 ]. The carbohydrates derived from marine algae benefit skin health [ 188 ].…”
Section: Marine-derived Compoundsmentioning
confidence: 99%